Long‐throw magnetron sputtering of amorphous Zn–Sn–O thin films at room temperature. Issue 7 (15th May 2015) - Frenzel, Heiko; Dörfler, Tobias; Schlupp, Peter; von Wenckstern, Holger; Grundmann, Marius
<x xml:space="preserve">Abstract</x> We report on the fabrication of amorphous zinc tin oxide (ZTO) thin films by long‐throw magnetron sputtering on glass substrate. This method is especially appropriate for the growth of amorphous oxides at room temperature. ZTO films were deposited from single ceramic target and via co‐sputtering of ZnO and SnO<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1m9pkrgs" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />2</alternatives> targets in inert Ar atmosphere only. Without additional annealing steps, the films showed a minimum resistivity of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1m9pkrf7" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />2.4×10−3Omega</alternatives>m and a maximum resistivity of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1m9pkrbk" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />5×102Omega</alternatives>m. The conductivity can be tuned via total pressure, power ratio in case of co‐sputtering and the applied substrate voltage from semiconducting to insulating. Furthermore, 30 nm thick ZTO films deposited at room temperature showed a mean transmittance of 90% in the visible spectral range, are X‐ray amorphous, and their surface roughness is as low as <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1m9pkr91" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />0.3</alternatives>nm. The application of these films is shown in the demonstration of an all amorphous oxide pn‐diode.